A Review On: Wound Healing - Kumar, Chanchal; Khan, Mr. Mohd. Shahid; Khinchi, M. P.; Khan, Mohd. Javed; Ansari, Ashiya (Asian Journal of Pharmaceutical Research and Development, 2017)
Wound healing is a biological process that begins with trauma and ends with scar formation. There are two types of tissue injury: full and partial thickness. Partial thickness injury is limited to the epidermis and superficial dermis, with no damage to the dermal blood vessels. Healing occurs by regeneration of other tissues. Full thickness injury involves loss of the dermis extends to deeper tissue layers, and disrupts dermal blood vessels. Wound healing involves the synthesis of several types of tissue and scar formation. The three phases of repair are lag, proliferative, and remodeling. Directly after injury, hemostasis is achieved with clot formation. The fibrin clot acts like a highway for the migration of cells into the wound site. Within the first four hours of injury, neutrophils begin to appear. These inflammatory cells kill microbes, and prevent the colonization of the wound. Next the monocyte, or macrophage, appears. Functions of these cells include the killing of microbes, the breakdown of wound debris, and the secretion of cytokines that initiate the proliferative phase of repair. Synthetic cells, or fibroblasts, proliferate and synthesize new connective tissue, replacing the transitional fibrin matrix. At this time, an efficient nutrient supply develops through the arborization (terminal branching) of adjacent blood vessels. This ingrowth of new blood vessels is called angiogenesis. This new and very vascular connective tissue is referred to as granulation tissue. The first phase of repair is called the lag or inflammatory phase. The inflammatory response is dependent on the depth and volume of tissue loss from the injury. Characteristics of the lag phase include acute inflammation and the initial appearance and infiltration of neutrophils. Neutrophils protect the host from microorganisms and infection. If inflammation is delayed or stopped, the wound becomes susceptible to infection and closure is delayed.Various plant species have served as a source of medicine for people all over the world, for year’s plant is one of the most intense areas of natural product research yet the field is far from being exhausted. Plant & their extract have immense potential for the management & treatment of wound.